The Effect of Sign Language on the Language Development of Deaf and Ha rd-of-Hearing Children: A Systematic Review - Jarollahi, Farnoush; Fallahnezhad, Tayyebe; Aslibeigi, Farideh (Journal of Modern Rehabilitation, 2025)
Introduction: To systematically review and evaluate the evidence regar ding the effect of sign language on language development in deaf and h ard-of-hearing children. Materials and Methods: A comprehensive search of electronic databases, including PubMed/ MEDLINE, Web of Science, S copus, EMBASE, Google Scholar, and ProQuest, from 1995 to April 2024, with no language restrictions, was conducted. Two authors independentl y assessed the risk of bias using the Newcastle-Ottawa scale (NOS). Re sults: Six studies involving 259 participants found that exposure to s ign language benefits language development in deaf children using hear ing aids or cochlear implants (CIs). Children exposed to sign language showed similar or even better spoken language skills than those with limited exposure to sign language. Encouraging parents to learn sign l anguage can significantly support deaf children’s communication and la nguage development. Conclusion: Deaf children with CIs benefit most fr om communication approaches tailored to their needs. Early interventio n, parental involvement, and a rich language environment (signed or sp oken) are crucial. While sign language exposure shows promise, further research is needed, especially on its long-term effects and use by he aring parents.
Keywords: Björn-2026-02-22